PHYSICAL ACTIVITY, PHYSICAL FITNESS AND ACADEMIC ACHIEVEMENT IN ADOLESCENTS: A SYSTEMATIC REVIEW - Rodriguez,Cristiano Copetti (2020)
ABSTRACT Objective: To synthesize the evidence available in the literature on the relationship between the components of physical activity, physical fitness and academic achievement in adolescents. Methods: The review followed the methodological procedures described by PRISMA and was carried out in the Lilacs, Medline, SciELO, PubMed, Web of Science and Science Direct databases. Quantitative empirical studies published as of 2006 were included. The following descriptors and keywords were used: “Motor activity”, “Physical fitness”, “Physical activity”, “Educational status”, “Academic achievement”, “Academic performance”, and their equivalents in Portuguese and Spanish. Results: The most widely investigated variable was physical fitness (45.5%) followed by physical activity (40.9%), whereas only three studies (13.6%) investigated both. Conclusion: Physical activity and physical fitness are positively associated with the academic achievement of adolescents. In more than 80% of studies the association was considered strong. The physical fitness component most frequently associated with academic achievement was cardiorespiratory fitness. Level of evidence II; Systematic review.